Penguasaan Kalimat Anak Usia Dini di TK Aisyiyah 14 Padang - Asri Wahyuni Sari; Syahrul R; Novia Juita (Fakultas Bahasa dan Seni UNP, 2013)
Abstract: This article was written to describe the master of Indonesian sentences for children in the age of 4,0-5,0 years old at the kindergarten of Aisyiyah 14 Padang based on (1) the amount of clauses, (2) the form of syntax, (3) the subject function, (4) the auxiliary completed, (5) the negation form. The data of this research was speech act to the children in the age of 4,0-5,0 years old at the kindergarten of Aisyiyah 14 Padang. Data was collected by using fishing technique, listening provided by speaking technique, unaware recording technique, writing technique and recording technique. The result of this research showed that the children have already mastered the type of singular, sentences verbal, adjectival, nominal, frase preposisional, transitive, intransitive, semitransitive, dwitransitive, ekatransitive, declararative, interrogative, imperative, exclamative, major, minor, active, passive and negative sentence. So, they has got preoperational process. Their sentences have had complex sentences that more than 5-8 wordsKey words: Penguasaan, kalimat bahasa Indonesia,anak usia dini